Open-Distance Education as a Mechanism for Sustainable Development: Reflections on the Nigerian Experience - Aderinoye, Rashid; Ojokheta, Kester (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2004)
This article examines open-distance learning in Nigeria and the role it plays in personal, community, and national development. Following consultation with existing literature, a qualitative survey was conducted using questionnaires, interviews, and participatory experience. Although particular emphasis was paid to the Nigerian context, the findings in this article may be regarded as reflective distance education experiences elsewhere in Africa. Clearly, education is the key to human development and progress. It is essential to bring about changes in attitudes, values, and behaviour. Used ethically, distance education may enable people to make informed choices about their present life and future. Moreover, these assertions have been credited to many scholars and institutions at one time or the other. The question here, however, is: To what extent are these assertions true of education, and more especially of those individuals benefiting from open and distance learning in Nigeria? This and more incisive issues constitute the substance of this article.